Same-sex sexual identity development in an Indian context - Kumar Pandya, Apurva; Pandya, Siddhi; das Nair, Roshan (British Psychological Society, 2013)
One of the challenges of writing a chapter on inter sectionality, with a specific emphasis on sexuality and ethnicity, is that specificity distorts the ideal of inter sectionality, which seeks to see people as multiple composites of identities, not simply two or three of these. However, the pragmatics of understanding some of these intersections in depth does require us to develop a focus. This chapter, therefore, seeks to investigate the experiences, dilemmas, challenges and triumphs of being a sexual and ethnic minority. Using case studies and narratives from clinical encounters, research studies, web-blogs, and mass media, I chronicle these accounts to understand the complex psychological and political journeys people caught between seemingly conflicting identities have to make on a daily basis.